2023
DOI: 10.1002/psc.3475
|View full text |Cite
|
Sign up to set email alerts
|

Glucopeptides derived from myelin‐relevant proteins and hyperglucosylated nontypeable Haemophilus influenzae bacterial adhesin cross‐react with multiple sclerosis specific antibodies: A step forward in the identification of native autoantigens in multiple sclerosis

Abstract: Multiple sclerosis (MS) is an inflammatory and autoimmune disorder, in which an antibody‐mediated demyelination mechanism plays a critical role. We prepared two glucosylated peptides derived from the human myelin proteins, that is, oligodendrocyte‐myelin glycoprotein (OMGp) and reticulon‐4 receptor (RTN4R), selected by a bioinformatic approach for their conformational homology with CSF114(Glc), a designed β‐turn antigenic probe derived from myelin oligodendrocyte glycoprotein (MOG), a glycoprotein present in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The peptides were synthesized using the Liberty Blue automated microwave peptide synthesizer (CEM Corporation, Matthews, NC, USA) following the Fmoc/tBu strategy and using Tentagel S RAM resin (loading 0.23 mmol/g) as previously described. 52 The following Fmoc-amino acids were used: Fmoc-Ala-OH, Fmoc-Asp(tBu)-OH, Fmoc-Glu(tBu)-OH, Fmoc-Phe-OH, Fmoc-His(Trt)-OH, Fmoc-Lys(Boc)-OH, Fmoc-Leu-OH, Fmoc-Asn(Trt)-OH, Fmoc-Gln(Trt), Fmoc-Thr(tBu)-OH, Fmoc-Tyr(tBu)-OH, Fmoc-Nle(ε-N 3 )-OH, and Fmoc-Pra-OH. The Fmoc deprotections were performed using a solution of 20% piperidine in DMF (2 M).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The peptides were synthesized using the Liberty Blue automated microwave peptide synthesizer (CEM Corporation, Matthews, NC, USA) following the Fmoc/tBu strategy and using Tentagel S RAM resin (loading 0.23 mmol/g) as previously described. 52 The following Fmoc-amino acids were used: Fmoc-Ala-OH, Fmoc-Asp(tBu)-OH, Fmoc-Glu(tBu)-OH, Fmoc-Phe-OH, Fmoc-His(Trt)-OH, Fmoc-Lys(Boc)-OH, Fmoc-Leu-OH, Fmoc-Asn(Trt)-OH, Fmoc-Gln(Trt), Fmoc-Thr(tBu)-OH, Fmoc-Tyr(tBu)-OH, Fmoc-Nle(ε-N 3 )-OH, and Fmoc-Pra-OH. The Fmoc deprotections were performed using a solution of 20% piperidine in DMF (2 M).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is an immunologically controlled, inflammatory disease of the central nervous system (CNS) characterized by myelin damage 1,2 . Moreover, MS patient antibodies recognize glucopeptides derived from human myelin proteins 3 . Many studies have shown that myelin oligodendrocyte glycoprotein (MOG) is an important autoantigen that is associated with MS and experimental autoimmune encephalomyelitis (EAE: an animal model for T cell‐mediated inflammatory and demyelinating diseases) 4,5 .…”
Section: Introductionmentioning
confidence: 99%